IOT APPLICATION IN THE PRODUCTION OF WHITE PEPPER BERRIES - Mohamad Asrul, Mustapha (MPB, 2021)
Iot application in pepper industry is still relatively new especially in the production of white pepper berries. The traditional process of producing white pepper berries has certain drawbacks especially in maintaining the quality of water during the soaking process. With the establishment of IoT application in the production of white pepper berries, it will improve the standards of production by monitoring the quality of water used and thus improve the final quality of white pepper.